2021
DOI: 10.3390/ijerph18136823
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Periodontitis on Dementia and Cognitive Impairment: A Meta-Analysis

Abstract: The association between periodontal disease and dementia/cognitive impairment continues to receive increasing attention. However, whether periodontal disease is a risk factor for dementia/cognitive impairment is still uncertain. This meta-analysis was conducted to comprehensively analyze the effect of periodontitis on dementia and cognitive impairment, and to assess the periodontal status of dementia patients at the same time. A literature search was undertaken on 19 October 2020 using PubMed, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 75 publications
(186 reference statements)
2
24
0
1
Order By: Relevance
“…Accordingly, the results of this study are in line with the most recent comparative subgroup analysis of twenty observational studies, carried out by Guo et al [ 7 ], who found a strong relationship between periodontitis and cognitive decline (OR = 1.77, 95% CI: 1.31–2.38). The analysis of subgroups (severity of PDS) showed that moderate/severe periodontitis was associated with dementia (OR = 2.13).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, the results of this study are in line with the most recent comparative subgroup analysis of twenty observational studies, carried out by Guo et al [ 7 ], who found a strong relationship between periodontitis and cognitive decline (OR = 1.77, 95% CI: 1.31–2.38). The analysis of subgroups (severity of PDS) showed that moderate/severe periodontitis was associated with dementia (OR = 2.13).…”
Section: Discussionsupporting
confidence: 92%
“…There is therefore a need for critical data analysis of the presence and magnitude of association between these two conditions. The hypothetical relationship between the status of periodontium and cognitive state has been thoroughly investigated over the last two decades using systematic reviews [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their findings also revealed that periodontal disease was associated with dementia events (34). Additionally, a recent meta-analysis by Guo et al disclosed that there is a correlation between periodontitis and cognitive impairment, and moderate or severe periodontitis is a risk factor for dementia, consistent with our findings (93). The exact molecular mechanism of the involvement of periodontitis in the pathogenicity of dementia remains ambiguous, and the possible explanations are detailed as follows.…”
Section: Comparison With Other Studies and Possible Explanationssupporting
confidence: 91%
“…Previous studies have suggested that chronic inflammatory stimulation is involved in the pathophysiological mechanism of cognitive frailty [ 27 ]. In addition, the most important reason for tooth loss in older individuals is the long-term cumulative effects of periodontitis [ 28 ]. Oral pathogens and their toxic molecules, after disseminating into the bloodstream, may induce a low-grade systemic inflammation through upregulating the release of cytokines and inflammatory mediators, which can trigger neuroinflammation and cause neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%